Panbiogeographic analysis of some Cactaceae from Ecuador [Análisis panbiogeográfico de algunas Cactaceae del Ecuador] - Morrone, J. (2017)
The geographical distributions of 12 species of Cactaceae assigned to five genera were analyzed using a panbiogeographic approach to identify their biogeographic patterns and contribute to the study of the biogeographical relationships of the flora from Ecuador. The selected species are distributed mainly in the dry forests of northern Peru and southern Ecuador. Based on the track analysis, three generalized tracks (dry coastal, central-northern interandean and southern interandean) and one node were identified, the latter in the overlap of the second and third tracks at the biogeographic province Western Ecuador.